2021
DOI: 10.3389/fcosc.2021.734931
|View full text |Cite
|
Sign up to set email alerts
|

Large Cities Fall Behind in “Neighborhood Biodiversity”

Abstract: Urbanization is a major driver of global species loss. While cities with suitable habitats and conservation policies may support locally-high biodiversity levels, we suspected that the complexity of managing very large cities might counteract the advantage of large geographic area, and these cities may be less effective at biodiversity conservation. To answer this, we examined the relationship between the number of native indicator wildlife species (mean and maximum) in 112 cities across three metropolitan are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Previous research have explored the effect of land cover types for biodiversity in urban areas using varying grid sizes from 0.1 to 50 Km finding contrasting results on the direction of the effect. Studies performed at 1 Km 2 -a scale explored in our study -found mammal (Gallo et al, 2017;Hursh et al, 2023) and arthropod richness (Fenoglio et al, 2020) declined with urban cover, in line with our findings in the case of arthropods and contrary to our findings in the case of mammals for two of our cities (Groningen and Amsterdam), and species richness increased with the size of green areas (Cooper et al, 2021), in line with our findings for just one of cities explored (Rotterdam). Finally, studies performed at higher resolution (0.01 Km 2 ) found a general trend in increase of species richness with increasing distance to the core of the city (Sweet et al, 2022;Aznarez et al, 2022).…”
Section: From Data To Assessmentssupporting
confidence: 91%
“…Previous research have explored the effect of land cover types for biodiversity in urban areas using varying grid sizes from 0.1 to 50 Km finding contrasting results on the direction of the effect. Studies performed at 1 Km 2 -a scale explored in our study -found mammal (Gallo et al, 2017;Hursh et al, 2023) and arthropod richness (Fenoglio et al, 2020) declined with urban cover, in line with our findings in the case of arthropods and contrary to our findings in the case of mammals for two of our cities (Groningen and Amsterdam), and species richness increased with the size of green areas (Cooper et al, 2021), in line with our findings for just one of cities explored (Rotterdam). Finally, studies performed at higher resolution (0.01 Km 2 ) found a general trend in increase of species richness with increasing distance to the core of the city (Sweet et al, 2022;Aznarez et al, 2022).…”
Section: From Data To Assessmentssupporting
confidence: 91%
“…Previous studies have explored the effect of land cover types for biodiversity in urban areas using varying grid sizes from 0.1 to 50 Km nding contrasting results on the direction of the effect; negative effect of urban areas on bird diversity at 50 km 2 (Ferenc et al 2014). Studies performed at 1 km 2 -a scale explored in our study-found negative effect of urban cover on mammal (Gallo et al 2017;Hursh et al 2023) and arthropod richness (Fenoglio, Rossetti, and Videla 2020), in line with our ndings in the case of arthropods and contrary to our ndings in the case of mammals and for two of our cities (Groningen and Amsterdam), and a positive effect on species richness when looking at speci cally the size of green areas (Cooper et al 2021), in line with our ndings for just one of cities explored (Rotterdam). Finally, studies performed at higher resolution (0.01 Km2) found a general trend in increase of species richness with increasing distance to the core of the city (Sweet et…”
Section: From Data To Assessmentssupporting
confidence: 88%
“… 17 Urban green spaces that are rich in biodiversity more often benefit wealthier areas in large cities. 18 , 19 The informal settlements of some large low- and middle-income country cities also experience more extreme weather-related mortality, morbidity and displacement. 20 …”
Section: Introductionmentioning
confidence: 99%